EFEKTIVITAS PELAYANAN KESEHATAN DI PUSKESMAS NAGRAK KECAMATAN NAGRAK KABUPATEN SUKABUMI - Maximianus Ardon Bidi; Dina Deviana Anggraeni (STISIP Widyapuri Mandiri Sukabumi, 2024)
The effectiveness of health services at the Nagrak Health Center is not fully effective. Due to the ineffectiveness of the services provided by medical personnel. Therefore the author is interested in taking the title Effectiveness of Health Services at the Nagrak Health Center, Nagrak District, Sukabumi Regency with an effectiveness theory approach, Saxena in Indrawijaya (2014: 176) states that: Effectiveness is a measure that states how far the target (quantity, quality, time) is achieved achieved. The greater the target achieved, the higher the level of effectiveness. method used in this study uses a qualitative research method of descriptive analysis. With the focus of this study on the Effectiveness of Health Services, where the scope of analysis unit is in the Nagrak Health Center, Nagrak District, the number of informants in this study is 6 people, using purposive sampling and snowball sampling. While the informants for this study were the Head of the Community Health Center, Health Workers, Administrative Officers and the Community. While data collection techniques with interviews, observation, and documentation. For data validation, using source triangulation, technical triangulation, and time triangulation. While data analysis is done by processing data, presenting data, reducing data, and drawing conclusions/verification. Based on the research results it is known that the better the health service, the more effective the service. While the effectiveness of health services at the Nagrak Community Health Center, Nagrak District, Sukabumi Regency, can be optimized by making improvements in terms of service so that it is more effective for the community, so that the effectiveness of health services can be achieved.